Analysis of the Effect of Altitude Variation on the Production Quality of Sidimpuan Salak (Salacca sumatrana Becc.) in South Tapanuli Regency - Surya Handayani; Siti Mardiana; Syahbuddin Hasibuan (Universitas Muhammadiyah Palembang, 2026)
Fruit quality is a key indicator in determining the market value of Salak Sidimpuan. One environmental factor influencing fruit quality is the altitude of the growing site. This study aimed to analyze the effect of altitude variations on the quality of Salak Sidimpuan (Salacca sumatrana Becc.) fruit in South Tapanuli Regency. A quantitative approach with a comparative design was employed. The sample consisted of 30 *salak* orchards grouped into three altitude zones: lowlands (0–300 m asl), mid-elevations (300–700 m asl), and highlands (>700 m asl). Quality parameters analyzed included sugar content (°Brix), fruit weight, vitamin C content, total acidity, fruit skin color, and the percentage of marketable fruit. Data were analyzed using ANOVA followed by the Tukey test at a 5% significance level. The results showed that altitude significantly affected all fruit quality parameters (p<0.05). Mid-elevation areas produced the best quality, yielding the highest sugar content (18.6°Brix), greatest fruit weight (62.4 g), highest vitamin C content (8.9 mg/100 g), and highest percentage of marketable fruit (87%). Conversely, lowlands exhibited the lowest quality, while highlands fell into the intermediate category. Thus, altitude is a crucial factor in determining Salak Sidimpuan quality, with the optimal range found in mid-elevation areas.